IMPLEMENTATION OF AUDIOVISUAL TO INCREASE KNOWLEDGE OF ANEMIA IN ADOLESCENT GIRLS: A CASE STUDY - Fatmawati, Fatmawati; Aisah, Siti (Journal of Vocational Nursing, 2025)
Introduction: Effective and efficient media is needed to support nutrition education so that the information conveyed can be well received by its targets. Knowledge about anemia in adolescent girls is often underestimated, so the potential for the development of this disease continues. Lack of understanding about anemia in adolescent girls causes them to have unhealthy eating habits.  One of the interesting media is video which includes the use of animated images, videos, or sounds (audio). The aim study is to investigate the effect of Anemia Prevention Education Using Animated Videos on Knowledge about Adolescent Girls at SMA N 15 Semarang. Methods: The case study method uses a descriptive design with a nursing process approach. The interventions were pre- and post-tests with a sample size of 10 respondents. The educational intervention used animated video media which was played for ± 10 minutes with 2 animated video series. The subjects of this case study are young women who were taken using purposive sampling techniques under the specified inclusion and exclusion criteria. Evaluation is measured using Hb levels before and after the session. Results: There was a significant change in participants’ knowledge after using animated videos, namely being in a good category (≥10. Conclusions: The results of this study show that providing education using animation media effectively increases knowledge and Hb levels.